2018
DOI: 10.17265/1934-7359/2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Air-entrained Concrete: Relationship between Thermal Conductivity and Pore Distribution Analyzed by X-Ray Tomography

Abstract: The thermal conductivity values of ordinary concrete can be adjusted to those prescribed in constructions by entraining air bubbles to reduce the density of concrete in order to achieve good thermal insulation. This paper concerns the analysis of air bubble distribution in concrete obtained by micro X-ray µCT (computed tomography) and correlates it with its thermal conductivity (k). The samples were prepared of ordinary concrete varying the density by air-entraining additives, ranging between 2,277 kg/m 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, thermal conductivity of concrete can be influenced by the pore distribution and entrained air volume in the mix design. Pore distribution analysis using x-ray tomography demonstrated that, air entrainment can be used as a sealer for thermal insulation [4]. It was also shown that in the wet state, the k value is higher due to the exceedance of air entrainer that leads to coalescing of bubbles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thermal conductivity of concrete can be influenced by the pore distribution and entrained air volume in the mix design. Pore distribution analysis using x-ray tomography demonstrated that, air entrainment can be used as a sealer for thermal insulation [4]. It was also shown that in the wet state, the k value is higher due to the exceedance of air entrainer that leads to coalescing of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that in the wet state, the k value is higher due to the exceedance of air entrainer that leads to coalescing of bubbles. However, higher air volume reduces the density and negatively affects mechanical performance [4]. A separate study was conducted to determine how k value changes with variables such as admixture type and content (like fly ash and slag), coarse and fine aggregate type and content, age, temperature, water-to-cement ratio, and humidity condition, etc.…”
Section: Introductionmentioning
confidence: 99%